Effects of Y2O3–RE2O3 (RE = Sm, Gd, Lu) Additives on Electrical and Thermal Properties of Silicon Carbide Ceramics. Issue 1 (3rd October 2015) - Jang, Seung Hoon; Kim, Young‐Wook; Kim, Kwang Joo; Lee, Seoung‐Jae; Lim, Kwang‐Young
Abstract : In this study, we investigated the electrical and thermal properties of SiC ceramics with 2 vol% equimolar Y2 O3 –RE2 O3 (RE = Sm, Gd, Lu) additives. The three SiC ceramics with 2 vol% equimolar Y2 O3 –RE2 O3 additives showed electrical conductivities on the order of ~10 3 (Ω·m) −1, which is one order of magnitude higher than that of the SiC ceramics sintered with 2 vol% Y2 O3 only. The increase in electrical conductivity is attributed to the growth of heavily nitrogen‐doped SiC grains during sintering and the confinement of oxide additives in the junction area. The thermal conductivities of the SiC ceramics were in the 176–198 W·(m·K) −1 range at room temperature. The new additive systems, equimolar Y2 O3 –RE2 O3, are beneficial for achieving both high electrical conductivity and high thermal conductivity in SiC ceramics.